2018
DOI: 10.1055/a-0717-5411
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade Serous Ovarian Carcinoma

Abstract: In the early 2000s a two-tier grading system was introduced for serous ovarian cancer. Since then, we have increasingly come to accept that low-grade serous ovarian carcinoma (LGSOC) is a separate entity with a unique mutational landscape and clinical behaviour. As less than 10% of serous carcinomas of the ovary are low-grade, they are present in only a small number of patients in clinical trials for ovarian cancer. Therefore the current treatment of LGSOC is based on smaller trials, retrospective series, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
1
24
0
3
Order By: Relevance
“…Our findings at diagnosis where M2 TAMs are increased at metastatic sites is in line with previous literature data showing that M2 increase the invasiveness of ovarian cancer [24] and that TAM behavior, number, and composition differ according to the tumor area (demonstrated in different solid tumors, but not yet in ovarian cancer [25]). Although often treated similarly, low-grade tumors respond differently to chemotherapy compared to high-grade tumors [26], differ genetically [27], and have a different immune biology. The group of Yang et al demonstrated, based on the retrospective analysis of micro-array datasets, that the gene signature of immune cells is nearly opposite in high-grade serous ovarian cancer compared to low-grade serous ovarian cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings at diagnosis where M2 TAMs are increased at metastatic sites is in line with previous literature data showing that M2 increase the invasiveness of ovarian cancer [24] and that TAM behavior, number, and composition differ according to the tumor area (demonstrated in different solid tumors, but not yet in ovarian cancer [25]). Although often treated similarly, low-grade tumors respond differently to chemotherapy compared to high-grade tumors [26], differ genetically [27], and have a different immune biology. The group of Yang et al demonstrated, based on the retrospective analysis of micro-array datasets, that the gene signature of immune cells is nearly opposite in high-grade serous ovarian cancer compared to low-grade serous ovarian cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…62 For recurrent LGSOCs, secondary cytoreductive surgery (SCRS) should be considered based on the time to recurrence, disease localization, number of metastases, and patient general condition. 52 SCRS without macroscopic residual disease is associated with significant better PFS and OS of 60.3 months and 167.5 months, respectively, compared to 10.7 months and 88.9 months, respectively, in patients with macroscopic residual disease after SCRS. 52 LGSOCs have poor response to conventional chemotherapy; as a result, some studies have suggested the use of bevacizumab in conjunction with platinum-based and non-platinum-based chemotherapy.…”
Section: Treatmentmentioning
confidence: 84%
“…52 SCRS without macroscopic residual disease is associated with significant better PFS and OS of 60.3 months and 167.5 months, respectively, compared to 10.7 months and 88.9 months, respectively, in patients with macroscopic residual disease after SCRS. 52 LGSOCs have poor response to conventional chemotherapy; as a result, some studies have suggested the use of bevacizumab in conjunction with platinum-based and non-platinum-based chemotherapy. 63 Schmeler and colleagues 64 evaluated 17 patients with recurrent…”
Section: Treatmentmentioning
confidence: 84%
See 2 more Smart Citations